2020
DOI: 10.1002/mbo3.1104
|View full text |Cite
|
Sign up to set email alerts
|

Hexyl gallate for the control of citrus canker caused by Xanthomonas citri subsp citri

Abstract: Brazil is the biggest producer of sweet oranges and the main exporter of concentrated orange juice in the world. Among the diseases that affect citriculture, Asiatic citrus canker, caused by the bacterial pathogen Xanthomonas citri, represents one of the most significant threats. The current Brazilian legislation regulating the control of citrus canker no longer requires the eradication of affected trees in states where the incidence of the disease is high. Instead, control involves disease control measures, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…Penicillic acid had a protective effect on leaves similar to the effect observed by Cavalca et al (2020) with the application of hexyl gallate (600 µg ml −1 ) for citrus canker treatment where the mean of lesions observed for the compound was of 0.5 lesions/cm². Maxwell et al (2019) also reported a ternary zinc chelate solution (TSOL) at 800 µg ml −1 with similar results to copper chemicals in a 3‐year study conducted in greenhouse and field conditions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Penicillic acid had a protective effect on leaves similar to the effect observed by Cavalca et al (2020) with the application of hexyl gallate (600 µg ml −1 ) for citrus canker treatment where the mean of lesions observed for the compound was of 0.5 lesions/cm². Maxwell et al (2019) also reported a ternary zinc chelate solution (TSOL) at 800 µg ml −1 with similar results to copper chemicals in a 3‐year study conducted in greenhouse and field conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Penicillic acid had a mean of 0.437 lesions/cm² (SE ± 0.087), when applied at 25 µg ml −1 , while the positive control, with application equivalent to 700 µg ml −1 of metallic copper, showed values of 0.270 lesions/cm² (SE ± 0.080) and in the negative control the mean was 1.772 lesions/cm² (SE ± 0.294). Penicillic acid had a protective effect on leaves similar to the effect observed by Cavalca et al (2020) with the application of hexyl gallate (600 µg ml −1 ) for citrus canker treatment where the mean of lesions observed for the compound was of 0.5 lesions/cm². Maxwell et al (2019) also reported a ternary zinc chelate solution (TSOL) at 800 µg ml −1 with similar results to copper chemicals in a 3year study conducted in greenhouse and field conditions.…”
Section: Discussionsupporting
confidence: 66%
“…Panels C and G in Figure 2 correspond to the negative control cells with intact membrane and panels D and H to positive control cells with permeabilized membrane. Membrane disruption has also been highlighted as the main mode of action of phenolic molecules with antimicrobial activity by several other studies [ 17 , 18 , 19 , 20 , 21 ], including anti- X. citri compounds previously reported by our group [ 3 , 4 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 55%
“…At the end of the experiments, leaves were detached and digitalized at 600 dpi. The software ImageJ was used to evaluate bacterial infection and infection severity, which were expressed as the number of citrus canker lesions formed per square centimetre of leaf (lesions per cm 2 ) as described by Cavalca et al (2020). The data obtained were submitted to nonparametrical statistical analysis of Kruskal-Wallis (Dunn), with three degrees of freedom using the software BioEstat 4.…”
Section: Pathogenicity Testsmentioning
confidence: 99%